Model design of general hospitals in the interwar period on the example of the hospital in Puławy - Przesmycka, Natalia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
As a result of research and discussions of medicine doctors and architects involved in the development of health service in the interwar period, model solutions were developed to optimize the functional systems of hospitals, as well their size, organization, architectural and construction solutions. Due to the outbreak of World War II, few assumptions have been fully implemented. The building in Puławy is a unique investment in Poland, because it was used to implement the idea of a rational and modern small general hospital, and such hospitals were lacking in the reborn Poland the most. The aim of the research is to show the architectural value of the building of the present pavilion B in the SPZOZ complex in Puławy as an implementation of a design solution containing the latest ideas of the interwar period in the field of shaping general hospitals.